PENGARUH LINGKUNGAN KERJA FISIK DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. PESONA PUTRA PERKASA KOTA TANGERANG SELATAN - Noviati Friska Zai; Isep Amas Priatna (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine the effect of the physical work environment and organizational culture on employee job satisfaction. The research method used is a quantitative approach with an associative research type. The population in this study consists of all permanent employees of PT Pesona Putra Perkasa city tangrang selatan, totaling 58 people, all of whom were taken as samples using a saturated sampling technique. Data were collected through questionnaires that had been tested for validity and reliability, then analyzed using SPSS version 24 with multiple linear regression tests, t-test, F-test, and the coefficient of determination. The results of the study also show that there is a significant influence between Physical Work Environment and Employee Job Satisfaction, with a significance value of 0.015 (<0.05) and a t-count of 2.514 > 2.00324 (t-table). The simple regression equation is Y = 3.842 + 0.900X1. Furthermore, the results of the study show that there is a significant influence between Organizational Culture and Employee Job Satisfaction, with a significance value of 0.05 (<0.05) and a t-count of 2.893 > 2.00324 (t-table). The simple regression equation is Y = 3.077 + 0.930X2.